2017
DOI: 10.1002/ejic.201700623
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclam‐Based Fluorescent Ligand as a Molecular Beacon for Cu2+ and H2S Detection

Abstract: A pentadentate cage‐like cyclam‐based fluorescent ligand has been designed, synthesized, and characterized by 1D and 2D NMR spectroscopic analysis. To further characterize the title ligand, ESI‐MS, UV/Vis spectroscopy, and fluorescence experiments have been also performed. Its suitability as a chemosensor for the detection of Cu2+ ions has been successfully explored with a variety of spectroscopic techniques (i.e., ESI‐MS, UV/Vis, and fluorescence). A Job's plot experiment, together with ESI‐MS experiments, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…A somewhat different behavior was observed in the case of HS − : the demetalation of macrocyclic Cu 2+ complexes induced by HS − was previously reported and even exploited for the detection of this anion [ 82 , 83 , 84 ]; therefore, its effect on the decomposition of [Cu( 2 )] 2+ and [Cu( 3 )] 2+ could be expected. To limit the possible interference of HS − , its concentration level was kept the same as sulfite in the corresponding competition test.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…A somewhat different behavior was observed in the case of HS − : the demetalation of macrocyclic Cu 2+ complexes induced by HS − was previously reported and even exploited for the detection of this anion [ 82 , 83 , 84 ]; therefore, its effect on the decomposition of [Cu( 2 )] 2+ and [Cu( 3 )] 2+ could be expected. To limit the possible interference of HS − , its concentration level was kept the same as sulfite in the corresponding competition test.…”
Section: Resultsmentioning
confidence: 87%
“…Their emission properties are controlled by the coordinated metal center and its oxidation state [ 78 ]. In particular, due to the well-known fluorescence-quenching behavior of copper(II) [ 81 , 82 , 83 , 84 ], [Cu(azacyclam)] 2+ complexes prepared with luminescent LF s display only a very poor emission.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorescence enhancement observed at 470 nm suggested that a demetallation reaction occurred. 108 In 2017, Hu's group synthesized an anthraquinone-based derivative probe 77 containing N,S heteroatoms, which was selectively quenched by Cu 2+ in a 1 : 1 ratio and exclusively recovered by the subsequent addition of S 2À , producing a strong red fluorescence at 610 nm. 109 Also, in 2018, Liu et al synthesized probes 78-1, 78-2, and 78-3 for the recognition of H 2 S by functionalizing triarylboron with cyclen and diphenylamine.…”
Section: Copper-based Triggersmentioning
confidence: 99%
“…Motivated by our interest in the reactivity of H 2 S/HS – towards transition metals and aiming at studying it in a more biocompatible context (i.e. with the metal center embedded in a protein), we selected the 14 kDa Cu‐protein azurin from Pseudomonas aeruginosa as a test system.…”
Section: Introductionmentioning
confidence: 99%
“…colorimetry, electrochemistry and chromatography) a large number of H 2 S fluorescent probes have been devised in the last few years. [45][46][47][48][49] Motivated by our interest in the reactivity of H 2 S/HStowards transition metals [50][51][52][53] and aiming at studying it in a more biocompatible context (i.e. with the metal center embedded in a protein), we selected the 14 kDa Cu-protein azurin from Pseudomonas aeruginosa as a test system.…”
Section: Introductionmentioning
confidence: 99%